2014
DOI: 10.1074/jbc.m113.547018
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ1 Connects the Cell Membrane Pathway to the Nuclear Receptor Pathway in Insect Steroid Hormone Signaling

Abstract: Background: PLCG1 plays an important role in calcium signaling. Results: PLCG1 up-regulates 20E-induced calcium signaling and regulates USP1 PKC phosphorylation in the lepidopteran insect Helicoverpa armigera. Conclusion: 20E activates PLCG1 to induce calcium influx to regulate USP1 PKC phosphorylation for gene expression. Significance: Our study establishes a link between the nongenomic pathway and genomic pathway in steroid hormone 20E signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 52 publications
3
65
0
Order By: Relevance
“…Recent studies have shown that ultraspiracle (USP, a component of the functional ecdysteroid receptor complex) is phosphorylated by PKC in Drosophila (42). In H. armigera, it seems that the 20E-induced phosphorylation of USP relies on the function of PLC and Ca 2+ influx (43). Although different isoforms of PKC and PLC may be involved in 20E and JH signaling, it is possible that JH uses the membrane-initiated signaling to influence the cell responses to 20E.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ultraspiracle (USP, a component of the functional ecdysteroid receptor complex) is phosphorylated by PKC in Drosophila (42). In H. armigera, it seems that the 20E-induced phosphorylation of USP relies on the function of PLC and Ca 2+ influx (43). Although different isoforms of PKC and PLC may be involved in 20E and JH signaling, it is possible that JH uses the membrane-initiated signaling to influence the cell responses to 20E.…”
Section: Discussionmentioning
confidence: 99%
“…20E mediates CDK10 phosphorylation to enhance formation of the EcRB1/USP1 transcription complex 36 . 20E via GPCR-, PLC-, Ca 21 -, and PKC-signaling mediates USP1 phosphorylation for gene transcription 12 . At the downstream of ligand activated-GPCR, PLC hydrolyzes phosphatidylinositol 4,5-bisphosphate to generate inositol 1,4,5-triphosphate (IP3) and diacylglycerol (DAG) 37 .…”
Section: Discussionmentioning
confidence: 99%
“…IP3 binds to its receptor in the endoplasmic reticulum membrane to drive the release of intracellular calcium ions, whereas DAG and Ca 21 bind to the protein kinase C (PKC) to activate PKC 38 . 20E via PKC regulates CDK10 11 and USP1 phosphorylation to form the EcR/USP transcription complex 12 . In the current study, the larvae died before pupation or delayed pupation after knockdown of ErGPCR-2, suggesting that ErGPCR-2 is involved in gene transcription and metamorphosis in the 20E pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 20E-induced cell responses have been reported in our previous studies. 36 In summary CKS1 promotes midgut regenerative cell proliferation during the larval growth stage to increase midgut cell number, thereby increasing midgut size for nutrient absorption and larval growth. Insulin (via InR, PI3K, and AKT) promotes CKS1 expression Figure 9.…”
Section: Cks1 Expression Was Coordinately Regulated By Insulin and 20ementioning
confidence: 99%